Determination of Characterization and Evaluation of Probiotic Fish Feed - M. Abareethan; A. Amsath (New Visions in Biological Science Vol. 4, 2021)
Administration of probiotic feed like Bacillus subtilis, Lactococcus lactis, Saccharomyces cerevisiae in the diets confer beneficial effect to the host animal. In this study the nutritional value of probiotic feed and its utilization are studed. The probiotics alter the enzymes, microbial metabolism and improve the weight gain and survival rate. Probiotic diets are being incorporated together with prebiotics in recent years. Probiotics with synbiotics elicit synergistic and more favorable actions. Increased advantage of formulated probiotic and its benefits in maintaining good water quality and rapid increase in growth of L. rohita were evaluated and characterized in this study, promising feed and novel strategy to be used in aquaculture from this research study. The selection of probiotics in aquaculture improved growth, attachment to the intestinal mucus and production of beneficial compounds can be considered for improving the growth.